The implementation of digital storytelling in an online classroom to help promoting students’ critical thinking skills - Maulana, Cepri; Setyarini, Sri; Wirza, Yanty (Jurnal Pendidikan Bahasa dan Sastra, 2021)
Over the last few months, the Covid-19 pandemic has turned traditional learning into online learning. As a result, EFL teachers are expected to utilize digital technology to aid students to meet learning objectives. Through digital technology, EFL teachers could select their learning strategy, including storytelling, in their instructional practices. This study portrays the implementation of digital storytelling in EFL online classrooms and the student's critical thinking skills promoted by the learning strategy. The study employs the case study qualitative method. The data was collected through observation and interview by utilizing an observation checklist as well as a list of questions. The study reveals that the implementation of digital storytelling was conveyed in a proper step by optimizing various media. The students also show positive responses through their active engagement during the learning process. In addition, students can develop their critical thinking skills by presenting their ideas and active discussion with their friends.